Evaluation of outflow temperatures generated by a dry heat fluid warmer at low fluid rates. (September 2022) - Badham, Hannah L.; Clark, Louise; Gibson, Sarah
Abstract: Objective: To evaluate the output temperature of a dry heat fluid warmer at fluid rates typically used in small animal veterinary patients. Study design: Prospective in vitr o study. Animals: None. Methods: Ambient temperature lactated Ringer's (17.9-18.8 °C) was delivered via a dry heat fluid warmer. A temperature probe was used to measure fluid outflow temperature from the compatible giving set at 5, 10, 20, 50, 70, 80, 100, 200, 300, 400 and 500 mL hour –1 . Outflow fluid temperature at plateau (two consecutive readings within 0.1 °C) was compared with baseline fluid temperature (fluid warmer turned off) to calculate temperature changes at each rate. Kruskal–Wallis test was used to compare changes in temperature and time to plateau temperature. Dunn's post hoc test was used to test for significant differences in temperature compared to 5 mL hour –1 ; p value < 0.05. Results: Median plateau outflow temperature increased as fluid rate increased, with temperatures of 18.5, 18.6, 18.7, 18.8, 19.4, 19.4, 21.5, 25.3, 28.5, 30.7 and 32.6 °C, at flow rates of 5, 10, 20, 50, 70, 80, 100, 200, 300, 400 and 500 mL hour –1 . Fluid rates > 100 mL hour –1 showed significant increases from baseline ( p  = 0.021) There was no difference in temperature change from baseline at fluid rates < 100 mL hour –1 ( p > 0.05). Compared to plateau temperature at 5 mL hour -1, there was a statistical difference in plateau temperature above 100 mL hour –1 (p = 0.0207). Maximum outflow plateau temperature was 32.6 °C at 500 mL hour –1 . Conclusions and clinical relevance: A dry heat fluid warmer has significantly decreased efficacy at low fluid rates, with no statistically significant increase in fluid temperature at fluid rates below 100 mL hour –1 at the end of a compatible fluid line. Inline dry heat fluid warmers are ineffective at fluid rates below 100 mL hour –1 .